2016
DOI: 10.1177/0306624x16677784
|View full text |Cite
|
Sign up to set email alerts
|

Calculating Probability in Sex Offender Risk Assessment

Abstract: Risk is the probability of an adverse event or outcome. In a previous article, I compared the Bayesian and Frequentist models of defining probability. This article compares the Bayesian and regression models of quantifying probability. Both approaches are widely used in the biomedical and behavioral sciences even though they yield different results. No consensus has emerged as to which is more appropriate. The choice between them remains controversial. This article concludes that the Bayesian model provides a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Most DHS evaluators use the Static-99R, but their independence means each evaluator can use it in different ways to predict risk. They can choose risk groups from either the 2009 or 2015 samples and can predict risk by either logistic regression (Elwood et al, 2017; Phenix et al, 2015) or Bayesian posterior probabilities (Elwood, 2018). Some DHS evaluators augment the Static-99R with other scales, such as the VRS-SO (Violence Risk Scale–Sexual Offender Version; Olver, Beggs-Christofferson, Grace, & Wong, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Most DHS evaluators use the Static-99R, but their independence means each evaluator can use it in different ways to predict risk. They can choose risk groups from either the 2009 or 2015 samples and can predict risk by either logistic regression (Elwood et al, 2017; Phenix et al, 2015) or Bayesian posterior probabilities (Elwood, 2018). Some DHS evaluators augment the Static-99R with other scales, such as the VRS-SO (Violence Risk Scale–Sexual Offender Version; Olver, Beggs-Christofferson, Grace, & Wong, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For this study, p (EA|IPV, CA) = ( p (EA∩IPV∩CA))/( p (IPV∩CA)), where p (EA|IPV, CA) is the conditioned probability of experiencing EA given a history of IPV and/or CA. Monte Carlo simulation was calculated, and the credible interval (CI) for each conditional probability [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Margin of error is critical in sex offender risk assessment, particularly when forensic decisions are based on an absolute risk threshold (Elwood, 2016b). Like any sample statistic, an OR has a margin of error.…”
Section: Extrapolating Actuarial Ratesmentioning
confidence: 99%
“…Accordingly, risk assessment is inherently nomothetic, not idiographic. When evaluators incorporate an external risk factor, they make an empirical judgment about a reference class, rather than a clinical judgment about an individual (Elwood, 2016b; Imrey & Dawid, 2015). Kahneman and Tversky (1973) found that people rightly consider the group base rate when it is the only information they have but typically ignore the base rate when given more information, even when the additional information is irrelevant.…”
Section: Clinical Overrides Of Actuarial Ratesmentioning
confidence: 99%